Fun and Fair: Influencing Turn-taking in a Multi-party Game with a Virtual Agent - Andrist, Sean; Leite, Iolanda; Lehman, Jill (IDC '13 Proceedings of the 12th International Conference on Interaction Design and Children, 2013)
Language-based interfaces for children hold great promise in education, therapy, and entertainment. An important subset of these interfaces includes those with a virtual agent that mediates the interaction. When participants are groups of children, the agent will need to exert a certain amount of turn-taking control to ensure that all group members participate and benefit from the experience, but must do so without being so overtly directive as to undermine the children's enjoyment of and engagement in the task. We present a hierarchy of nonverbal and verbal behaviors that a virtual agent can employ flexibly when passing the conversational turn. When used effectively, these behaviors can equalize participation, and potentially decrease the amount of overlapping speech among participants, improving automatic speech recognition in turn. We evaluated the behaviors by having children play a language-based game twice, once with a flexible host and once with an inflexible host that did not have access to the behaviors. Post-game opinion cards revealed no difference between the conditions with respect to fun or likability of the host, despite the flexible agent eliciting more evenly distributed play.